Comparison of Low and High Dosage Regime of Oxytocin for Uterine Contraction in Elective Caesarean Sections Performed Under Spinal Anaesthesia - Rizvi, Syed Ali Mazhar; Riaz, Azmat; Khan, Fatima Sharif; Malik, Tariq Mehmood; Yaqub, Umairah; Amjad, Muhammad Fawaz (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare low dose intravenous to high dose during elective Cesarean Sections.Study Design: Quasi-experimental study.Place and Duration of Study: Main Operation Theatre, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Apr to May 2022.Methodology: A total of two hundred term pregnant women were randomized to either 5 IU intravenous bolus group or 10 IU intravenous bolus group of Oxytocin. The difference in Hemoglobin levels (Pre-op minus post-op), tachycardia percentage, tone of uterus and need for additional “rescue” uterotonic doses/ agents, hypotension and post Oxytocin administration vomiting were assessed.Results: The primary outcome was efficacy of both drugs in causing uterine contraction. There were 6(6.1%) patients in Low dose group who developed uterine atony while there were 5(5.3%) patients who developed uterine atony in group High dose. There were 18(18.4%) patients who developed partially inadequate uterine contraction in group LD versus 15(15.8%) patients in Group HD. There were 74(75.5%) patients who developed adequate contraction in group LD versus 75(78.9%) patients in group HD who developed adequate contraction with p-value of 0.850. The frequency of side effects was also comparable in both study groups. The estimated blood loss was as mean drop in hemoglobin was 1.77±.42 grams per deciliter in group LD versus 1.49±0.50 grams per deciliter in group HD with p-value of 0.469.Conclusion: We concluded that use of low dose of oxytocin has similar efficacy in causing uterine contraction compared to high dose.